2020
DOI: 10.3390/agronomy10091296
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Analysis of Anthocyanin-Related Genes in Wild-Type Blueberry and the Pink-Fruited Mutant Cultivar ‘Pink Lemonade’: New Insights into Anthocyanin Biosynthesis

Abstract: Blueberries are one of the richest sources of antioxidants, such as anthocyanins, among fruits and vegetables. Anthocyanin mutants, like the pink-fruited cultivar ‘Pink Lemonade’, are valuable resources for investigating anthocyanin biosynthesis in blueberries. In this study, we examined expression of flavonoid pathway genes during fruit development in wild-type, blue-fruited blueberries using quantitative real-time PCR. Expression was also compared between wild-type and the pink-fruited ‘Pink Lemonade’. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…From the two bilberry MYBA‐type TFs showing the direct regulation of anthocyanin biosynthesis, only VmMYBA1 seems to have this role in berries, corroborating earlier results of VcMYBA in blueberry (Plunkett et al ., 2018; Die et al ., 2020). The newly identified gene family member, VmMYBA2 , was mainly expressed in unripe berries and other plant tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the two bilberry MYBA‐type TFs showing the direct regulation of anthocyanin biosynthesis, only VmMYBA1 seems to have this role in berries, corroborating earlier results of VcMYBA in blueberry (Plunkett et al ., 2018; Die et al ., 2020). The newly identified gene family member, VmMYBA2 , was mainly expressed in unripe berries and other plant tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In blueberries, MYBAtype TFs of highbush blueberry (Vaccinium corymbosum) and rabbiteye blueberry (Vaccinium virgatum syn. ashei) were shown recently as activators of anthocyanin accumulation (Plunkett et al, 2018;Die et al, 2020), while VcMYBPA1 has earlier been indicated in PA biosynthesis (Zifkin et al, 2012). Our earlier studies on Vaccinium species have suggested a role for MYBPA1type TF in anthocyanin biosynthesis in V. uliginosum (Primetta et al, 2015), V. myrtillus (Jaakola et al, 2010) and in blueberry skin (G€ unther et al, 2020) where MYBPA1 expression is positively correlated with anthocyanin accumulation.…”
Section: Introductionmentioning
confidence: 94%
“…A high number of DEGs representing MYB and bHLH genes was found from our RNA‐seq libraries, indicating that their regulation is strongly influenced by the light spectral quality. MYBA‐ type TFs have been identified as the key regulators activating anthocyanin biosynthesis in fruits including Vaccinium berries (Die, Jones, Ogde, Ehlenfeldt, & Rowland, 2020; Plunkett et al, 2018). In addition, MYBPA1 has been suggested to have a regulatory role in anthocyanin biosynthesis based on our previous studies (Primetta et al, 2015; Günther et al, 2020; Karppinen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, some previous researchers only recorded the development of anthocyanin content in already ripened fruit [8], rather than the changes from unripe to ripe fruits, as presented here. This development of anthocyanin content during the ripening process occurs as a temporally-dependent extension of the flavonoid synthesis pathway, primarily controlled by the transcription factor MYB1 [14].…”
Section: Changes In Anthocyanin Content and Antioxidant Capacity During Maturationmentioning
confidence: 99%